A hybrid epithelial-mesenchymal transition program enables basal epithelial cells to bypass stress-induced stasis and contributes to a metaplastic breast cancer progenitor state - Joseph A. Caruso; Chira Chen-Tanyolac; Thea D. Tlsty (Breast Cancer Research, 2024)
Abstract Background Human mammary epithelial cell (HMEC) cultures encounter a stress-associated barrier termed stasis, during which most cells adopt a senescence-like phenotype. From these cultures, rare variants emerge from the basal epithelial population, re-initiating growth. Variants exhibit pre-malignant properties, including an aberrant epigenetic program that enables continued proliferation and acquisition of genetic changes. Following oncogenic transformation, variants produce tumors that recapitulate the histopathological characteristics of metaplastic breast cancer (MBC), a rare and aggressive subtype marked by the differentiation of neoplastic epithelium into squamous and mesenchymal elements. Methods Using a serum-free HMEC culture system, we probed the capacity for phenotypic plasticity inherent to basal epithelial cell populations from human breast tissue as they navigated stasis and emerged as variant populations. Results We observed robust activation of a TGF-β-dependent epithelial-mesenchymal transition (EMT) program in basal epithelial cells during stasis, followed by subsequent attenuation of this program in emerging variants. Inhibition of the TGF-β pathway or depleting the EMT regulators Snail or Slug allowed basal epithelial cells to collectively bypass stasis, demonstrating that cellular dysfunction and arrest resulting from TGF-β and EMT activation are central to this in vitro barrier. The spontaneous emergence of variants from stasis cultures was associated with a restricted EMT trajectory, characterized by the stabilization of hybrid EMT states associated with greater proliferative capacity, rather than progressing to a complete mesenchymal state characterized by irreversible growth arrest. Epigenetic mechanisms, which contributed to the dysregulated growth control characteristic of the variant phenotype, also contributed to the stability of the hybrid EMT program in variants. By overcoming the cellular dysfunction and growth arrest resulting from TGF-β and complete EMT, variants exhibited a higher oncogenic transformation efficiency compared to pre-stasis basal epithelial cells. Inhibiting the TGF-β pathway prior to stasis significantly reduced EMT in the basal epithelial population, alleviated selective pressure driving variant emergence, and also enhanced oncogenic transformation efficiency, resulting in tumors with markedly diminished metaplastic differentiation. Conclusions This study reveals how an epigenetic program governs basal epithelial cell fate decisions and contributes to the development of MBC progenitors by restricting access to terminal mesenchymal states that induce growth arrest and, instead, favoring hybrid EMT states with enhanced tumorigenic potential.